Role of iron oxide impurities in electrocatalysis by multiwall carbon nanotubes: An investigation using a novel magnetically modified ITO electrodes - Samant, Kanchan M.; Joshi, Vrushali S.; Patil, Kashinath R.; Haram, Santosh K. (Bulletin of Materials Science, 2014)
The role of iron oxide impurities in the electrocatalytic properties of multiwall carbon nanotubes (MWCNTs) prepared by catalytic chemical vapour decomposition method (CCVD) is studied in detail. A novel magnetically modified electrodes have been developed by which MWCNTs were immobilized on indium-tin oxide (ITO) electrodes, without any chemical binders. The electro-catalytic oxidation of dopamine, and reduction of hydrogen peroxide have been studied by cyclic voltammetry on magnetically modified electrodes with (i) MWCNTs with occluded iron oxide impurities (Fe-MWCNTs), (ii) MWCNTs grown on iron oxide nanoparticle particulate films (Io-MWCNTs) and (iii) pristine iron oxide nanoparticle particulate film (Io-NPs). A shift towards less positive potentials for the oxidation of dopamine was observed which is in the order of Fe-MWCNTs < Io-MWCNTs < Io-NPs. Similarly, trend towards less negative potentials for the reduction of hydrogen peroxide was observed. Thus, the electrocatalytic activities displayed by MWCNTs have been attributed to the iron oxide impurities associated with it. The systematic variation was related to the nature of interaction of iron oxide nanoparticles with MWCNT surface.
Keywords: dopamine; Hydrogen peroxide; iron oxide nanoparticles; magnetically-modified electrode; Multiwall carbon nanotubes (MWCNTs)

Green synthesis-mediated iron oxide nanoparticles using sphagneticola trilobata (L.) for antibacterial and anticancer assessment - Dhavale, Rakesh Pandit; Patil, Swapnil Sanjay; Jadhav, Sagar Ujwal; Dhavale, Rushikesh Pandit; Agawane, Sachin Bharat (Pharmacognosy Magazine, 2022)
Background: Green chemistry is widely accepted phenomenon to synthesize iron oxide nanoparticles (Fe-NPs) used in several biomedical and technological applications. Metal oxide nanoparticles are useful in biomedical, clearing environmental pollutants, enzyme immobilization, etc., Objectives: The synthesis of Fe-NPs using Sphagneticola trilobata leaf extract using ferric chloride solution and its biological assessment. Materials and Methods: The present study involved the synthesis of Fe-NPs using S. trilobata leaf extract using ferric chloride solution by the co-precipitation method. The synthesized nanoparticles were characterized for Fourier-transform infrared spectroscopy, scanning electron microscopy, powder X-ray diffraction spectroscopy, particle size analysis, and magnetization studies. The nanoparticles were biologically evaluated for microbiological, antioxidant, and in vitro cytotoxicity activity. Results: Magnetic nanoparticles were appeared in dark brown color. The change in color might result due to the presence of polyphenols in S. trilobata leaf extract. The characterization studies confirmed morphology, shape, and size of the nanoparticles. The mean diameter of Fe-NPs and S. trilobata-Fe-NPs was found to be 42.2 +/- 2.6 and 62.54 +/- 2.01 nm, respectively. Magnetization studies of nanoparticles revealed ferromagnetic behavior with the saturation magnetization at 57 emugm(-1). S. trilobata-Fe-NPs showed significant antibacterial action against Staphylococcus aureus and Bacillus subtilis by the well-diffusion method. Antioxidant activity of S. trilobata-Fe-NPs exhibited 65.78% inhibition in comparison with ascorbic acid. The cytotoxicity assay of S. trilobata-Fe-NPs on HCT-15 colon adenocarcinoma cells showed significant anticancer activity (56.44%) cytotoxic inhibition. Conclusion: Green synthesis-mediated S. trilobata-Fe-NPs appeared to produce significant antimicrobial and anticancer potential.
Keywords: Elemental analysis; field emission scanning electron microscopy; green synthesis; iron oxide nanoparticles; Sphagneticola trilobata; X-ray diffraction

Mechanistic insight into differential interactions of iron oxide nanoparticles with native, glycated albumin and their effect on erythrocytes parameters - Nisar, Akib; Ajabia, Devangi K.; Agrawal, Sanskruthi B.; Varma, Sanjana; Chaudhari, Bhushan P.; Tupe, Rashmi S. (International Journal of Biological Macromolecules, 2022)
Nanoparticles and protein bioconjugates have been studied for multiple biomedical applications. We sought to investigate the interaction and structural modifications of bovine serum albumin (BSA) with iron oxide nanoparticles (IONPs). The IONPs were green synthesized using E. crassipes aqueous leaf extract following characterization using transmission electron microscopy, energy dispersive X-ray analysis and X-ray diffraction. Two different concentrations of native/glycated albumin (0.5 and 1.5 mg/ml) with IONPs were allowed to interact for 1 h at 37 degrees C. Glycation markers, protein modification markers, cellular antioxidant, and hemolysis studies showed structural modifications and conformational changes in albumin due to the presence of IONPs. UV-visible absorbance resulted in hyperchromic and bathochromic effects of IONPs-BSA conjugates. Fluorescence measurements of tyrosine, tryptophan, advanced glycated end products, and ANS binding assay were promising and quenching effects proved IONPs-BSA conjugate formation. In FTIR of BSA-IONPs, transmittance was increased in amide A and B bands while decreased in amide I and II bands. In summary, native PAGE, HPLC, and FTIR analysis displayed a differential behaviour of IONPs with native and glycated BSA. These results provided an understanding of the interaction and structural modifications of glycated and native BSA which may provide fundamental repercussions in future studies.
Keywords: Albumin; Glycation; iron oxide nanoparticles